The Slavic dossier - Stamati, Iurie, author.
1 online resource.
Keywords: In The Slavic Dossier , Iurie Stamati’s objective is to understand the reasons for the emergence of two different discourses on the place of the Slavs on the territory of Moldova and their role in the genesis of Moldovans and their culture during the medieval period in the Soviet archaeology. His analysis goes beyond the utilitarian perception of Soviet archeology. To achieve this, Stamati not only questions the political contexts in which these discourses emerged, but also looks at the history of the Moldovan archaeological field, personal profiles of archaeologists, their theoretical and ideological attachment, relationships and interactions with each other inside and outside the archaeological field.